Limonite-hematite Composite High-phosphorus Iron Ores by Direct Reduction and Magnetic Separation - Minjin ZHU; Guang WANG; Qingshan YI; Jingsong WANG; Qingguo XUE (Kuangchan zonghe liyong)
In order to achieve the efficient utilization of a certain limonite-hematite composite high-phosphorus iron ore, experimental research was conducted on the preparation of iron concentrate based on a direct reduction-magnetic separation process. The results indicate that with an increase in temperature from 1 000 °C to 1 150 °C, the metallization ratio of the reduction pellets increased from 28.65% to 73.11%. With an increase in alkalinity from 0 to 1.2, the metallization ratio of the reduction pellets initially increased and then decreased, reaching a maximum of 76.52%. As the dosage of Na2CO3 in the pellets increased from 2% to 8%, the metallization ratio initially increased and then decreased, reaching a maximum of 74.36%. When a portion of the reducing agent was substituted with municipal solid waste, as the substitution ratio increased from 0 to 60%, the metallization ratio of the reduction pellets initially increased and then decreased, reaching a maximum metallization ratio of 83.64%. With an alkalinity of 0.6, Na2CO3 dosage of 4%, municipal solid waste substitution ratio of 20%, reduction temperature of 1 100 °C, and reduction time of 30 min, the metallization ratio of the pellets after reduction reached 83.64%. The previously reduced pellets were subjected to grinding and magnetic separation. With a grinding particle size of less than 0.03 mm and a magnetic field intensity of 100 kA/m, the concentrate yield, iron recovery rate, and metallization ratio after magnetic separation were 50.81%, 78.36%, and 48.81%, respectively. Due to the relatively small size of metallic iron particles, there is an overall lower concentrate yield and recovery rate. Further research on achieving the growth of metallic iron particles is crucial to address this issue.